Expeditious synthesis of pyrano[2, 3, 4-de]quinolines via Rh(iii)-catalyzed cascade C–H activation/annulation/lactonization of quinolin-4-ol with alkynes. Issue 55 (27th June 2017) - Liao, Gang; Song, Hong; Yin, Xue-Song; Shi, Bing-Feng
Abstract : One-step synthesis of tetracyclic pyrano[2, 3, 4- de ]quinolones via Rh(iii )-catalyzed cascade C–H activation/annulation/lactonization is described. Abstract : Rh(iii )-catalyzed cascade C–H activation/annulation/lactonization of quinoline-4-ols and alkynes has been reported. A broad range of tetracyclic pyrano[2, 3, 4- de ]quinolines have been prepared in one-step with good functional group tolerance, excellent site selectivity, and high efficiency.